Perencanaan Enterprise Architecture Pada Rumah Sakit Ibu Dan Anak Mulia Menggunakan Togaf Adm - Tri Widayanti (Jurnal Informatika dan Komputer, 2023)
Processing of patient data at the Mulia Mother and Child Hospital has so far been carried out on a paper-based basis and there has been no data integration between the registration, polyclinic, pharmacy and medical records departments. In order for better service and patient data processing to support decision making and provide fast and accurate information, enterprise architecture analysis and planning is needed. The aim of this research is enterprise architecture planning for information systems and information technology that will be applied to maternal and child hospitals in line with the vision and mission so that strategic objectives can be achieved. The research uses the Open Group Architecture Framework (TOGAF) method with the Architecture Development Method (ADM). TOGAF ADM has eight stages, this research only uses five stages, namely Preliminary, Architecture Vision, Business Architecture, Information System Architecture, and Technology Architecture. The research results are in the form of an information system and information technology blueprint that can support business processes to achieve the strategic goals expected by Mulia mother and child hospital. Apart from that, the TOGAF ADM method produces architectural designs according to the institution's vision and mission, so that it can overcome existing problems.